التقاطب المكتني و دلالته في أدب سعيد خطيبي رواية حطب سراييفو - منصور, هالة, باهي جهاد (University of El-oued, 2021)
كشفت هذه الدراسة عن تجربة روائية متميزة، لروائي سعيد خطيبي تمثلت في رواية " حطب سراييفو" وما حملته، من ثقافة بلدين مختلفين (الجزائر / البوسنة والهرسك) عقائديا، حضاريا، سياسيا، حيث اختصت بدراسة التقاطب المكاني من خلال إبراز كيفية التقابل بين الأمكنة والأمكنة المضادة لها، وقد تناولنا بالدرس ثنائيات عديدة متقابلة منها (ثنائية شمال / جنوب، اتصال / انفصال، مركز / هامش، الأليف/ معادي ...) وفي دراستنا حاولنا توضيح كيفية تشكيل معمار المكان الروائي من خلال، تبيين العلاقات بين الثنائيات الضدية، وتسرب هذا التقابل إلى الشخصية، فكان هناك علاقة متبادلة بينهما في التأثير والتأثر. هذا ما حاول البحث الوصول إليه، وإبرازه منذ بدايته إلى نهايته قدر المستطاع This study revealed a distinguished novelist experience, by the novelist Saeed Khatibi represented in the novel “The Firewood of Sarajevo” and what it carried, from the ideologicalcivil, and political culture of two countries (Algeria / Bosnia and Herzegovina) where it specialized in the study of spatial polarization by highlighting how places and places correspond The opposite of it, and we have dealt with in the lesson many opposite dichotomies of them (North/South dichotomy, connection/separation, center/periphery sympathetic/enemy...). In our study, we tried to clarify how to form the architecture of the novelistic place by clarifying the relationships between antagonistic binaries, and this correspondence leaked to the personality, so there was a reciprocal relationship between them in influence and vulnerability. This is what the research tried to reach, and to highlight it from its beginning to its end as much as possible.
Keywords: polarity, location, north/south, center/margin.; التقاطب، المكان، شمال/ جنوب، مركز /هامش